The therapeutic potential of targeting Oncostatin M and the interleukin-6 family in retinal diseases: A comprehensive review - Mori Tommaso; Nagaraj Nareshkumar Ragavachetty; Surico Pier Luigi; Zhou Wenjing; Parmar Uday Pratap Singh; D’Esposito Fabiana; Gagliano Caterina; Musa Mutali; Zeppieri Marco (Open Life Sciences)
Retinal diseases, which can lead to significant vision loss, are complex conditions involving various cellular and molecular mechanisms. The interleukin-6 (IL-6) family, particularly Oncostatin M (OSM), has garnered attention for their roles in retinal inflammation, angiogenesis, and neuroprotection. This comprehensive review explores the dual nature of OSM and other IL-6 family members in retinal pathophysiology, highlighting their contribution to both degenerative and regenerative processes. The review also examines current research on OSM’s interaction with key signaling pathways and discusses the potential of OSM and the IL-6 family as potential therapeutic targets. Understanding these mechanisms could lead to innovative treatments that modulate OSM activity, offering new avenues for managing retinal diseases and contributing to the development of more effective interventions.